The Endothelial Cell-Related Genes EIF1 and HSPA1B Contribute to the Pathogenesis of Alzheimer’s Disease by Modulating Peripheral Immunoinflammatory Responses - Yucheng Gu; Nihong Chen; Jingwen Qi; Lin Zhu; Xiangliang Chen; Feng Wang; Yingdong Zhang; Teng Jiang (Brain Sciences, 2025)
Background: Emerging evidence suggests that peripheral immunoinflammatory responses contribute to Alzheimer’s disease (AD) pathogenesis, and endothelial cells (ECs) are involved in these responses. Nevertheless, the potential molecular mechanisms and signaling pathways by which ECs modulate peripheral immunoinflammatory responses and thus contribute to AD pathogenesis are not fully understood. Methods: The single-cell RNA sequencing dataset GSE157827 was analyzed, and AD key genes were screened using LASSO regression and random forest algorithms. Functional enrichment analyses of these AD key genes were conducted using gene set enrichment analysis (GSEA) and gene set variation analysis. Immune cell infiltration analyses for AD key genes were performed using single-sample GSEA, and their correlations with immunoinflammatory factors were assessed using the TISIDB database. Peripheral blood RNA sequencing data from our cohort were utilized to validate the expression patterns of EC-related AD key genes in peripheral blood and to investigate their association with cognition. Results: ECs are the most significant contributors to AD among all brain cell subpopulations. For the first time, the EC-related genes EIF1 and HSPA1B were identified as key genes associated with AD progression. These two EC-related key genes may participate in AD pathogenesis by modulating peripheral immunoinflammatory responses. The levels of EIF1 and HSPA1B were significantly altered in the peripheral blood during AD progression, and EIF1 levels correlated with cognitive functions in AD clinical continuum patients. Conclusions: These findings underscore the critical roles of the EC-related genes EIF1 and HSPA1B in AD pathogenesis and their potential as biomarkers for this disease.